Effect of l-arginine addition on long-term storability of ram semen - Kaya, S. Ozer; Gur, S.; Kaya, E. (Wiley, 2018)
This study was conducted to investigate the effect of l-arginine addition on long-term storability of ram semen. Six Akkaraman rams were used as material. Semen samples were collected. Pooled samples were diluted and were divided into six equal aliquots. While aliquot 1 was kept as control, the stock solutions including 0.1, 0.5, 1, 5 and 10mm l-arginine were added to other aliquots. All aliquots were routinely frozen in 0.25-ml straws at -130 degrees C liquid nitrogen vapour and stored in liquid nitrogen -196 degrees C until being analysed. The equilibrated and thawed sperm motility, membrane integrity and arginase activity were evaluated. While the 10mm l-arginine supplementation significantly (p<.001) decreased equilibrated sperm motility, the 5mm significantly (p<.05) increased the membrane integrity and arginase activity in comparison with the control group. The motility (p<.001) and membrane integrity (p<.01) were determined to be highest in 0.5mm group, while significant reductions were observed in motility (p<.001) of 10mm group and arginase activity (p<.05) of 1, 10mm groups as compared to the control group. It was concluded that in vitro addition of 0.5mm l-arginine to ram semen may be useful, but 10mm may be harmful to spermatozoa quality during long-term storage.
Keywords: Arginase; cool storage; l-arginine; ram; semen